Effects of elastic band exercise on subjects with rounded shoulder posture and forward head posture - Kim, Tae-Woon (J Phys Ther Sci, 2016)
[Purpose] This study performed to investigate the effect of elastic band exercise program on the posture of subjects with rounded shoulder and forward head posture. [Subjects and Methods] The body length, forward shoulder angle, craniovertebral angle, and cranial rotation angle of participants (n=12) were measured before and after the exercise program. Furthermore, the thicknesses of the pectoralis major, rhomboid major, and upper trapezius were measured using an ultrasonographic imaging device. The exercises program was conducted with elastic bands, with 15 repetitions per set and 3 sets in total. [Results] The length of the pectoralis major, forward shoulder angle, and craniovertebral angle showed significant changes between before and after the exercise program, whereas the changes in the other measurements were not significant. The thickness of the upper trapezius showed a significant increase between before and after the elastic band exercise. [Conclusion] These findings suggest that the elastic band exercise program used in the study is effective for lengthening the pectoralis major and correcting rounded shoulder and forward head posture.